(untitled) (Annals of Medical Research, 2022)
Aim: The causative factors of neonatal feeding intolerance are poorly understood. Intrauterine environment and fetal conditions are important factors affecting gastrointestinal perfusion. Our aim was to evaluate whether maternal preeclampsia negatively affects preterm infants’ enteral feeding tolerability. Materials and Methods: Eight hundred and twenty preterm infants who were born between January 2015 and December 2016 and were under 1,500 grams and 30 weeks of gestational age were included in this entire cohort of which 701 were retrospectively analyzed because of missing records. Antenatal, perinatal, and neonatal outcome data were retrospectively analyzed. Results: There were statistical differences between infants with maternal preeclampsia (n=128) and without preeclampsia (n=573), in terms of mean birth weight, mean gestational age, grade 3-4 IVH, platelet count, being under 3rd percentile of body weight during discharge from NICU and feeding intolerance. There was no significant difference on the first day of feeding, fully enteral feeding days, and time of catch-up birth weight. After correcting the data with birth weight, gestational age, and SGA as a cofactor; nominal regression revealed that PE strongly may be an independent risk factor for FI in this study group [OR: 5.469 (95%CI 1.099-2.929) p:0.019]. Conclusion: According to this study’s results, we could say that preeclampsia is a significant risk factor for feeding intolerance in very low birth-weight preterm babies. For babies of mothers with preeclampsia, a nutrition plan should be made; interventions and treatments to minimize fetal effects should be investigated.